Editors' and authors' individual conflicts of interest disclosure and journal transparency. A cross-sectional study of high-impact medical specialty journals. Issue 7 (23rd July 2019) - Dal-Ré, Rafael; Caplan, Arthur L; Marusic, Ana
Abstract : Objective: To assess the fulfilment of authors' and editors' individual disclosure of potential conflicts of interest in a group of highly influential medicine journals across a variety of specialties. Design: Cross-sectional analysis. Setting and participants: Top-ranked five journals as per 2017 Journal Citation Report impact factor of 26 medical, surgery and imaging specialties. Interventions: Observational analysis. Primary and secondary outcome measures: Percentage of journals requiring disclosure of authors' and editors' individual potential conflicts of interest (CoI). Journals that were listed as followers of the International Committee of Medical Journal Editors (ICMJE) Recommendations, members of the Committee on Publication Ethics (COPE) and linked to a third party (ie, college, professional association/society, public institution). Results: Although 99% (129/130) of journals required author's CoI disclosure, only 12% (16/130) reported individual editors' potential CoIs. Forty−five per cent (58/130) of journals were followers of the ICMJE Recommendations, and 73% (95/130) were COPE members. Most (69%; 90/130) were linked to a college, professional society/association or public institution. Only one journal did not have policies on individual authors' and editors' CoI disclosure. Conclusion: Very few high-impact medical journals disclosed their editorial teams' individual potential CoIs—conversely, almost all required disclosure of authors' individual CoIs. Journal followers of the ICMJE Recommendations should regularly disclose the editors' individual CoIs, as this is the only legitimate way to ask the same transparency of authors.